Numerical and experimental comparison of 3D Particle Tracking Velocimetry (PTV) and Particle Image Velocimetry (PIV) accuracy for indoor airflow study. (1st May 2016) - Fu, Sijie; Biwole, Pascal Henry; Mathis, Christian
Abstract: Experimental measurement still plays an important role in indoor airflow study. To obtain three-dimensional and high-quality experimental data in building's indoor airflow study, Particle Tracking Velocimetry (PTV) and Particle Image Velocimetry (PIV) have been increasingly used. The accuracy and precision of measurement technologies is always a crucial issue. This paper first numerically compares the measuring performance of 3D PTV and typical 2D PIV algorithms on three laminar macro scale flows of known displacement, as a function of the particle tracking density defined as the ratio of mean particle spacing to mean particle displacement. Then, 3D PTV and 2D PIV results are compared using an experimental low-turbulence indoor airflow generated by a low-speed tailpipe. Results suggest that when the tracking density is smaller than two, 3D PTV generally cannot yield reliable measurement results. As the tracking density increases, 3D PTV has a better ability to measure larger displacement than PIV. Highlights: The effect of small tracking density on PIV and 3D PTV accuracy and precision is investigated using numerical method. An experimental low-turbulence indoor airflow is measured to compare results from typical PIV and 3D PTV technologies. When the tracking density is smaller than two, 3D PTV generally cannot yield reliable measurement results. As the tracking density increases, 3D PTV has a better ability to measure larger displacement than PIV.